Diversity of autoantibodies in patients with antimitochondrial antibody and their diagnostic value. Issue 2 (February 1987) - McMillan, S A; Alderdice, J M; McKee, C M; Dawson, A T; Callender, M E; Fulton, T T; Haire, M
Abstract : A retrospective analysis of clinical and laboratory features of 102 patients, whose sera contained antibody to mitochondria, showed that primary biliary cirrhosis was diagnosed in 50% of them. Immunofluorescence showed that the sera of the patients with primary biliary cirrhosis all had the M2 antimitochondrial antibody staining pattern. A new staining pattern, designated M2(1), which could be mistaken for the M2 pattern, was not found in any patients with either primary biliary cirrhosis or chronic active hepatitis. Other serological variables such as antibody to mitochondria in IgM class, to multiple nuclear dots, and to the XR antigen, were associated with primary biliary cirrhosis, and taken in association with antimitochondrial antibody of M2 type, contribute to the diagnosis of the disease.